A disparidade entre o discurso e a prática da responsabibilidade social: um balanço dos balanços sociais das maiores empresas do Brasil - Guimarães, Vitor Campos (2008)
The objective of this research is to verify the relation between the Social Report (SR) publication and the social investment values of the Brazilians Companies. We based our research using the universe ofthe '500 largest Anonymous Society (A.S.) non-financial companies' (Conjuntura Econômica Magazine, 2006) of Getúlio Vargas Foundation's ranking, utilizing the SR from the years of 2001 to 2005. From the Puppim de Oliveira's paper (2005), we could observe the variation of some social and environmental index, based on the IBASE SR. This variation was analyzed through the equivalences between Net profit (NP) and the Net Operational Revenue (NOR). The former analysis enabled us verify that there are disparities between the speech and the practice of Corporate Social Responsibility (CSR); through the similar observation of Ventura (2005) study's results about the social practices' institutionalization. The way to compare the SR publication frequency and the social investment, so as to reach this study object, were: (l) the verification of Brazilian's companies SR publication's frequency in year of 2005; (2) the calculation and comparison of the values published in the internaI social index, externaI social index and environmental index; (3) the observation of the former index equivalence according to the NOR and to the NP; (4) the SR publication's frequency verification based on the corporate sectors. The field's research contemplated the '500 largest A.S. nonfinanciaI companies', from the mentioned ranking, for the qualitative analysis development. The research also observed the sample comprised of 79 companies that published the IBASE model, so as to develop the quantitative analysis. We verified that the publication's frequency of SR grew considerably, between the years of 2001 and 2005, while the social investments values some times did not increase. So, the research revealed that the speech and the practice of social responsibility, based on the analyzed companies, did not pace at the same regularity, between the years of2001 and 2005.